Botryosphaeria dothidea: a latent pathogen of global importance to woody plant health - Marsberg, Angelica; Kemler, Martin; Jami, Fahimeh; Nagel, Jan H.; Postma‐Smidt, Alisa; Naidoo, Sanushka; Wingfield, Michael J.; Crous, Pedro W.; Spatafora, Joseph W.; Hesse, Cedar N.; Robbertse, Barbara; Slippers, Bernard (Molecular plant pathology, 2017)
Summary Botryosphaeria dothidea is the type species of Botryosphaeria (Botryosphaeriaceae, Botryosphaeriales). Fungi residing in this order are amongst the most widespread and important canker and dieback pathogens of trees worldwide, with B. dothidea one of the most common species on a large number of hosts. Its taxonomic circumscription has undergone substantial change in the past decade, making it difficult to interpret the large volume of literature linked to the name B. dothidea. This pathogen profile synthesizes the current understanding of B. dothidea pertaining to its distribution, host associations and role as a pathogen in managed and natural woody environments. The prolonged latent infection or endophytic phase is of particular importance, as it implies that the fungus can easily pass undetected by quarantine systems in traded living plants, fruits and other plant parts. Infections typically become obvious only under conditions of host stress, when disease symptoms develop. This study also considers the knowledge emerging from the recently sequenced B. dothidea genome, elucidating previously unknown aspects of the species, including mating and host infection strategies. Despite more than 150 years of research on B. dothidea, there is clearly much to be learned regarding this global tree pathogen. This is increasingly important given the stresses imposed on various woody hosts as a result of climate change. Taxonomy Botryosphaeria dothidea (Moug. ex Fr) Ces. & De Not, 1863. Kingdom Fungi, Phylum Ascomycota, Class Dothideomycetes, Order Botryosphaeriales, Family Botryosphaeriaceae, Genus Botryosphaeria, Species dothidea. Host range Confirmed on more than 24 host genera, including woody plants, such as Acacia (= Vachellia), Eucalyptus, Vitis and Pistachio. Disease symptoms Associated with twig, branch and stem cankers, tip and branch dieback, fruit rot, blue stain and plant death. Useful websites The Botryosphaeria site for detailed morphological descriptions (http://www.crem.fct.unl.pt/botryosphaeria_site/); Systematic Mycology and Microbiology Laboratory Fungal Database for all literature and associated hosts (https://nt.ars-grin.gov/fungaldatabases/); TreeBASE link for the combined ITS and TEF‐1α tree (http://purl.org/phylo/treebase/phylows/study/TB2:S18906); DOE Joint Genome Institute, JGI Mycocosm for the Botryosphaeria dothidea genome (http://genome.jgi.doe.gov/Botdo1_1/Botdo1_1.home.html).